2017
DOI: 10.3892/ol.2017.5898
|View full text |Cite
|
Sign up to set email alerts
|

Association between non-melanoma and melanoma skin cancer rates, vitamin D and latitude

Abstract: Abstract. Vitamin D synthesis takes place in the skin due to solar ultraviolet-B (UVB) radiation. Several studies have shown the association between low sun exposure, non-melanoma skin cancer (NMSC) and a lack of vitamin D synthesis. Since such synthesis in the body depends on the exposure of the skin to solar UVB radiation (290-320 nm), experimental measurements of this type of solar radiation are important. Tarapaca University in Arica, Chile, established a solar UV radiation laboratory in 2006 and since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
1
21
0
2
Order By: Relevance
“…Although the data demonstrated a more limited diversity of cancer subtypes than what has been published previously from a Florida cohort, the cancer profile after PD symptom onset was similar (24). It is plausible that unaccounted-for environmental factors, including latitude and sun exposure, play a role in this differential prevalence of cancers between cohorts (25,26).…”
Section: Discussionmentioning
confidence: 51%
“…Although the data demonstrated a more limited diversity of cancer subtypes than what has been published previously from a Florida cohort, the cancer profile after PD symptom onset was similar (24). It is plausible that unaccounted-for environmental factors, including latitude and sun exposure, play a role in this differential prevalence of cancers between cohorts (25,26).…”
Section: Discussionmentioning
confidence: 51%
“…In this study, we have also demonstrated a north-to-south gradient of increasing CMM incidence in Canada. While it was not possible to standardize the population by ethnic background to ensure comparison of homogenous populations, previous literature regarding the association of incidence of melanoma with latitude produced conflicting results, [31][32][33][34][35][36] with several studies noting a correlation between lower latitude and incidence of melanoma, whereas others reported no such correlation. 34 Our findings reinforce the previously regarded pattern that the incidence of CMM increases with geographic proximity to the equator in North America and highlights the continuity of trends between Canada and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…However, contradicting results have been reported in several studies. 6,[31][32][33][34][35][36] Many studies have indicated that decreasing latitude parallels increasing risk of CMM, whereas others suggested that latitude may in fact have an inverse relationship with CMM risk. 6,7,33,34,[37][38][39][40][41][42] Several studies have significantly contributed to the understanding of the epidemiology and risk factors for CMM in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is a deadly form of skin cancer ( Bertolotto, 2013 ; Weinstein et al, 2014 ) that is caused by the malignant transformation of melanocytes in the skin ( Uong & Zon, 2010 ; Bertolotto, 2013 ; Liu, Peng & Tobin, 2013 ). Melanoma accounts for less than 10% of all skin cancers, however it is associated with 80% of skin cancer related deaths ( Bandarchi et al, 2010 ; Bertolotto, 2013 ; Ramaraj & Cox, 2014 ; Leight et al, 2015 ; McCusker et al, 2017 ; Rivas et al, 2017 ). The early stage of a primary melanoma, where cancer cells are generally confined to the epidermis, is known as the radial growth phase (RGP) ( Clark, 1991 ; Meier et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%